PENDETEKSIAN KECURANGAN DALAM PERSPEKTIF ISLAM PADA AKUNTAN PUBLIK DI KOTA MEDAN - Asmaul - Husna; Sarwo - Edi; Widia - Astuty; Maya - Sari (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2021)
This study aims to determine, analyze and obtain empirical evidence of the effect of auditor experience, professional skepticism, and auditor independence on the ability of auditors to detect fraud in a public accounting firm in Medan. The population used in this study are auditors who work in public accounting firms in Medan, both head office and branch offices. The sample of this research is 63 auditors from 168 auditors who work in public accounting firms. The data collection technique used a questionnaire which was measured by a Likert scale. The analysis technique in this study uses the analysis of the Structural Equation Model (SEM) or the Structural Equation Model with the help of the Smart PLS version 3.0 program. The results showed that there was an influence from the variable auditor experience, professional skepticism, and auditor independence on the ability of auditors to detect fraud. The results of the analysis show that the experience of the auditor on the ability of the auditor to detect fraud has a path coefficient of 0.361. Professional skepticism about the auditor's ability to detect fraud has a path coefficient of 0.372. Auditor independence on the auditor's ability to detect fraud has a path coefficient of 0.229. For this reason, it is expected that auditors in carrying out audit assignments are given the opportunity to audit various types of companies in order to enhance the auditor's experience.